Frankincense oil-loaded nanoemulsion formulation of paclitaxel and erucin: A synergistic combination for ameliorating drug resistance in breast cancer: In vitro and in vivo study - Harneetpal Kaur; Kirandeep Kaur; Atamjit Singh; Neena Bedi; Balbir Singh; Mansour S. Alturki; Mohammed F. Aldawsari; Atiah H. Almalki; Atiah H. Almalki; Shafiul Haque; Hae-Jeung Lee; Dharmendra K. Yadav; et al. (Frontiers Media S.A., 2022)
Nanoformulation-based combinational drug delivery systems are well known to overcome drug resistance in cancer management. Among them, nanoemulsions are well-known and thermodynamically stable drug delivery systems suitable for carrying hydrophobic drugs and phytoconstituents to tackle drug-resistant cancers. In the present study, we have investigated the effect of paclitaxel in combination with erucin (natural isothiocyanate isolated from the seeds of Eruca sativa) loaded in the frankincense oil-based nanoemulsion formulation. The choice of frankincense oil for the current study was based on reported research investigations stating its magnificient therapeutic potential against breast cancer. Optimized nanoemulsion of paclitaxel (PTX) and erucin (ER) combination (EPNE) provided sustained release and exhibited enhanced cytotoxicity towards human epithelial breast cancer cells (T-47D) as compared to individual ER and PTX. EPNE was further assessed for its antitumor activity in the 7,12-dimethylbenz(a)anthracene (DMBA)-induced breast cancer mice model. EPNE significantly decreased the levels of hepatic and renal parameters along with oxidative stress in breast cancer mice. Furthermore, EPNE also showed decreased levels of inflammatory cytokines TNF-α, IL-6. Histopathological examinations revealed restoration of the tumorous breast to normal tissues in EPNE-treated breast cancer mice. Therefore, EPNE can act as a viable lead and therapeutic option for drug-resistant breast cancer.